Arrow-Fisher-Hanemann-Henry and Dixit-Pindyck Option Values Under Strategic Interactions - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2013)
We extend the Arrow–Fisher–Hanemann–Henry (AFHH) and Dixit–Pindyck (DP) option values to a game situation. By reinterpreting the AFHH option value as a change in the surplus from conservation because of the prospect of future information, we deal with a conceptual difficulty associated with the AFHH option value in the presence of strategic interactions. We then introduce the DP option value into a game situation. We show that the equivalence between the expected value of information and the DP option value in the standard model does not hold under strategic interactions.